A Coat Protein of the Bacteriophage M13 Virion Participates in Membrane-Oriented Synthesis of DNA - Jazwinski, S. Michal (1973)
Several molecules of a protein specified by gene 3 of M13 comprise a minor fraction of the phage coat and have been assigned a role in adsorption to the bacterial cell. We find that the gene-3 protein molecules of the virion are fully conserved in phage that have attached irreversibly to the host cell, and they form a complex with the phage DNA when it has been converted to a duplex replicative form. In cells infected at a restrictive temperature with a thermosensitive mutant in gene 3, there is no conversion of the phage DNA to the replicative form. Both the adsorbed phage and the complex of replicative form DNA with the gene-3 protein were isolated with the inner membrane fraction of the cell. We suggest that the gene-3 protein may perform an essential function in the synthesis of replicative form by linking the phage DNA to a cellular replicative system in or on the inner cell membrane.